Physical Activity and Sedentary Behavior of Elderly Populations during Confinement: Results from the FRENCH COVID-19 ONAPS Survey. Issue 5 (20th October 2021) - Chambonniere, C; Lambert, C; Tardieu, M; Fillon, A; Genin, P; Larras, B; Melsens, P; Baker, JS; Pereira, B; Tremblay, A; Thivel, D; Duclos, M
ABSTRACT: Introduction: A national confinement was imposed in France in March 2020 during 55 days to prevent the spread of the virus and protect vulnerable people such as older individuals. This study aimed to describe the movement behaviors, and their determinants, of elderly people (≥ 65 years) during the confinement. Methods: An online survey was conducted from April 1 st, 2020 to May 6 th, 2020 by the National Observatory for Physical Activity and Sedentary behaviors. This study compared the level of physical activity (PA), sitting and screen time before and during the confinement and identified the impact of initial PA, sedentary profiles of the participants and housing conditions. Results: 1, 178 people were included in this study. Reaching PA recommendations before lock-down was associated with the change in PA level during lock-down ( p < .001). Besides, geographic location was associated with the change in PA, sitting time and screen time during lock-down (respectively p = .03, p = .02, p = .02). Conclusion: This study confirm the negative impact of confinement on senior movement behaviors, whether or not they met with public health recommendations prior to the pandemic. The housing conditions of older people must be also taken into future public health policies.